2010
DOI: 10.1007/s10548-010-0150-1
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Propagation of Interictal Epileptiform Activity After Introduction of Levetiracetam Visualized with Electric Source Imaging

Abstract: Different neuroimaging techniques (fMRI, spectroscopy, PET) are being used to evaluate candidate drugs in pharmacological development. In patients with epilepsy fast propagation of the epileptiform activity between different brain areas occurs. Electric Source Imaging (ESI), in contrast to the aforementioned techniques, has a millisecond time resolution, allowing visualization of this fast propagation. The purpose of the current project was to use ESI to investigate whether introduction of an antiepileptic dru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…We have confirmed that interictal spikes can involve widespread networks, in line with previous studies showing that interictal epileptic activities can propagate rapidly in IEEG (Alarcon et al 1994) or in non-invasive electrophysiology (Larsson et al 2010;Tanaka et al 2010). Furthermore, we have shown that this is also the case for epileptic oscillations in the beta/low gamma band.…”
Section: Discussionsupporting
confidence: 90%
“…We have confirmed that interictal spikes can involve widespread networks, in line with previous studies showing that interictal epileptic activities can propagate rapidly in IEEG (Alarcon et al 1994) or in non-invasive electrophysiology (Larsson et al 2010;Tanaka et al 2010). Furthermore, we have shown that this is also the case for epileptic oscillations in the beta/low gamma band.…”
Section: Discussionsupporting
confidence: 90%
“…Also, it is noteworthy that frontal localisation was absent in our cases with focal ESES. It is possible that this contradictory finding obtained in our series may be due to the utilisation of dipole analysis and voltage mapping for source localisation which were applied on ESES spikes in a few previous studies [29, 31]. Self‐limited CECTS is the most frequent idiopathic focal epilepsy of childhood and is the most frequent epilepsy syndrome in school‐aged children. An increasing number of reports have previously shown a not so “benign” outcome and atypical evolution of this type of epilepsy.…”
Section: Resultsmentioning
confidence: 67%
“…Such authors have suggested that an improved combination of clinical data and computer-aided EEG analysis will offer an opportunity to recognize "dangerous" EEG features early in the course of the syndrome, and thus it may be possible to foresee (and possibly prevent) evolution into ESES in patients at risk, but without overt encephalopathy [10,21]. Although dipole analysis and source localisation have already been used in many previous studies for other childhood epileptic syndromes, such as Panayiotopoulos syndrome and self-limited CECTS [22][23][24][25][26][27][28], there are only very few studies in the literature that have utilised source analysis and spatio-temporal dynamics in ESES [19][20][21][22][23][24][25][26][27][28][29][30][31]. To our knowledge, until now, no serious efforts have been taken to classify EEG patterns in ESES based on the spatio-temporal dynamics of their spikes, in order to simplify the interpretation of these complicated EEG patterns.…”
mentioning
confidence: 99%
“…Clinical studies showed similar results emphasizing the large influence of LEV on seizure propagation. Larsson et al demonstrated that LEV significantly reduced the ratio of patients with epileptic spikes propagations from 22/24 to 7/15 (75). This may be due to the widespread expression of SV2A in the brain especially at regions vital for activity spreading and propagation including the dentate gyrus, entorhinal cortex, frontal cortex, several thalamic nuclei, and mesencephalon (106)(107)(108).…”
Section: Levetiracetam (Lev)mentioning
confidence: 99%